ANABOLIC STEROID ADVERSE EVENT PROFILE OBSERVED IN HEALTHCARE PROFESSIONALS - AHMAD , A; YOUSAF , AI; AHSAN , M; TAYYAB , M; AHMAD , O; ZEESHAN , M; HUSSAIN , AK; UMAR , M (Biological and Clinical Sciences Research Journal, 2024)
The misuse of anabolic-androgenic steroids (AAS) has become a significant public health concern, particularly among adult males and bodybuilders in Pakistan. Despite the increasing prevalence, limited data exist regarding the adverse effects of AAS and healthcare professionals’ perspectives on its misuse. Objective: To assess the adverse effects of AAS misuse as observed by healthcare professionals in Lahore, Pakistan, and to evaluate their experiences regarding self-medication, overdose, and ADR reporting. Methods: A cross-sectional survey was conducted from February to July 2023 among 203 healthcare professionals, including physicians, pharmacists, nurses, psychologists, and nutritionists. Participants were randomly selected from public and private hospitals and clinics in Lahore. Data were collected using a structured, prevalidated questionnaire distributed via Google Forms. Descriptive statistics, including frequencies and percentages, were analyzed using SPSS version 26.0. Results: AAS misuse was predominantly observed among males (82.8%) and adults (81.3%), with bodybuilders being the primary users (50.7%). The most common adverse effects included hypertension (52.7%), gynecomastia (60.6%), mood disorders (63.5%), and acne (65.5%). Self-medication (60.6%) and overdose (59.6%) were strongly associated with these adverse effects (p<0.001). ADR reporting to regulatory authorities was notably low, with only 27.1% of professionals reporting observed complications. Conclusion: This study highlights the widespread misuse of AAS and its associated adverse effects, particularly among males and bodybuilders in Lahore. The findings emphasize the urgent need for educational interventions, stricter regulatory policies, and improved ADR reporting mechanisms to address this public health issue effectively.